Time-lapse seismic analysis of focused fluid flow on the Vestnesa Ridge - Mathisen, Lena Myreng (UiT The Arctic University of Norway, 2016)
The Vestnesa Ridge is a large sediment drift at water depths of 1200-1300 meter and is the northernmost known gas hydrate province that exists along the Arctic continental margin. Several pockmarks connected to vertical fluid flow features are present at the crest of the Vestnesa Ridge. The fluid flow pierce through the gas hydrate stability zone and interrupt the bottom simulating reflection (BSR) originating from the transition zone between stable gas hydrates and free gas. Gas seeps into the water column from several pockmarks demonstrating that the fluid flow system is very active. The abundance of fluid-flow structures and the activity of this system make this an excellent area to study the genesis and mechanisms of focused fluid flow and their related geological processes. A unique approach to gain new knowledge about fluid flow systems in the subsurface is by use of 4D time-lapse seismic data that may help to better understand how these systems develop over relatively short periods of time. The feasibility of high-resolution 3D seismic data with a broad frequency bandwidth of up to 350 Hz for time-lapse studies has not yet been established. High resolution P-Cable 3D seismic data has been acquired over the eastern segment of the ridge in 2012 and repeated in 2013 and 2015. These three seismic surveys have been 4D processed side-by-side in order to highlight subsurface fluid-induced changes. In this thesis, a 4D processing workflow is developed in order to match the seismic data from the three surveys. The 4D processing steps included re-binning of geometry, time and phase matching, shaping filter, shallow statics correction and time-variant shifts. Several 4D attributes are used to quantify the repeatability of the 4D seismic data, the two main attributes being normalized root mean square (NRMS) and predictability (PRED). The NRMS value, for both of the repeats (2015-2012 and 2013-2012), improved significantly during the full processing workflow, while the PRED only changed minimal. PRED is more sensitive ...